HYPOPRESSIVE ABDOMINAL GYMNASTICS AND THE MANAGEMENT OF POST-PARTUM LOW BACK PAIN:CASE OF 64 PRIMIPARES UNDER 20 YEARS OF PORTO-NOVO - DOSSOU, Sémako Gérard; LAWANI, MOHAMED MANSOUROU; HOUETO, Vignon Gratien (My University, 2020)
One of the consequences of pregnancy and childbirth is postpartum low back pain. Its prevalence remains very high both in postpartum women (2/3) and in the general population. This musculoskeletal pain can persist for up to three (3) years, that is, until the arrival of a new pregnancy. It is therefore necessary to manage this pain. All the works in the literature are unanimous on the fact that there can be no treatment for low back pain without strengthening the abdominal and spinal muscles. However, because of the co-contraction of the abdominal and pelvic muscles, the abdominal muscles can only be strengthened by hypopressive techniques on the perineum. This experimental comparative study brought together 64 continuous primary low back pain women who gave birth by the vaginal route. Our objective is to assess the effectiveness of hypopressive abdominal gymnastics in the management of postpartum lumbar pain in women under the age of twenty from the city of Porto-Novo. The results showed that hypopressive abdominal gymnastics promotes the toning of the abdominal strap and the significant reduction in pain and functional disability linked to low back pain. There is no doubt that hypopressive gymnastics is a very effective method of managing lowback pain in the postpartum period.
Keywords: Hypopressive gymnastics; Low back pain; Postpartum; Primiparous; Benin